The Eurasian hot nightlife: Environmental forces associated with nocturnality in lizards. Issue 11 (10th October 2017) - Vidan, Enav; Roll, Uri; Bauer, Aaron; Grismer, Lee; Guo, Peng; Maza, Erez; Novosolov, Maria; Sindaco, Roberto; Wagner, Philipp; Belmaker, Jonathan; Meiri, Shai
Abstract: Aim: Lizards are ancestrally diurnal, and most of them remain so. Nocturnality is common among lizards, but the environmental factors associated with lizard nocturnal activity are still unknown. Here, we contrasted the ambient temperature and productivity hypotheses, where we predicted that cold temperatures will pose a stonger limit to nocturnal species richness than diurnal lizards. Moreover, we contrasted the relative importance of annual, day and night mean temperatures to pinpoint the drivers of nocturnal lizard richness. Location: Mainland Eurasia. Methods: We collected distribution range and activity time data for all 1, 113 lizard species found throughout mainland Eurasia. This represents the largest geographical scope to date, for studies of lizard species richness. We examined the spatial patterns of nocturnal species richness in relationship to diurnal species richness across environmental gradients of ambient temperature and productivity. Results: Nocturnal lizards are richest in the tropics and in deserts, and their richness decreases with latitude. However, nocturnal lizards are absent from the highest latitudes and coldest regions inhabited by lizards. Diurnal and nocturnal lizards respond in a similar manner to climatic factors. Ambient temperature has a strong influence on both, whereas productivity is more tightly related to the proportion of nocturnal species. Main conclusions: Nocturnality is widespread among Eurasian lizards. However, nocturnal lizards are absent from invariably cold regions, and low temperatures seem to be a limiting factor for lizard activity period. We suggest that the year‐round warm nights of the tropics reduce the cost of being active at night and open the nocturnal niche for many lizards. In hot deserts, the combination of hot days and aridity increases the cost of diurnal activity, whereas nocturnal activity provides a shelter from these extreme conditions.